Creativity and Creative Industries in Regional Australia Interconnected Networks, Shared Knowledge and Choice Making Agents - McIntyre, Phillip; Kerrigan, Susan; Fulton, Janet; King, Evelyn; Williams, Claire (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book explores the relationship between creativity, creative people, and creative industries in regional Australia through examining lived experience. The authors draw on more than 100 qualitative interviews with creative workers, and contextualise this creative work within the broader social and cultural structures of Australia's Hunter region (located north of Sydney, in New South Wales). An invaluable resource for anyone interested in creative ecosystems as well as creativity and innovation, this book is an ethnographic study using the Hunter region as a case connected to the national and global networks that typify the creative industry. This timely addition to the Palgrave Studies in Creativity and Culture series gives a unique insight into creativity and cultural production. Phillip McIntyre is a Professor in the School of Humanities, Creative Industries and Social Sciences at the University of Newcastle, Australia. A communication and media scholar, his research focuses on creativity and innovation. Susan Kerrigan is Professor and Chair of the Department of Film, Games and Animation at Swinburne University of Technology, Australia. An expert in the fields of creative practice and screen production, her research highlights creative agents and how their practices produce creative products that are culturally consumed. Janet Fulton is Adjunct Associate Professor at the Royal Melbourne Institute of Technology (RMIT), Australia. Her research interests include creativity and cultural production, journalism, journalism education, media entrepreneurship and work-integrated-learning. Evelyn King worked in schools and academia before tackling PR at the Australian Museum. She has experience in cultural and heritage tourism, economic development, smart city initiatives, renewable energy and business start-ups. Claire Williams is a writer and editor. Formerly Faculty Director Creative Industries at Hunter TAFE, she has also taught Communications, Information Studies and HR at tertiary level. She is also an actor and theatre director working in stage and film.
Chapter 1: Introduction -- Chapter 2: Creativity and the Creative Industries: History and Context -- Chapter 3: Creative Industries: Global and Local Perspectives -- Chapter 4: Statistical Analysis -- Chapter 5: Music -- Chapter 6: Performing Arts -- Chapter 7: Architecture -- Chapter 8: Visual Arts -- Chapter 9: Fashion -- Chapter 10: Advertising, PR and Design -- Chapter 11: Publishing -- Chapter 12: Radio -- Chapter 13: Film and Television -- Chapter 14: Electronic Games and Interactive Content -- Chapter 15: Support Organizations, Education and Training -- Chapter 16: Conclusion.
Keywords: Psychology, Industrial; Industries; Economics; Culture; Culture -- Study and teaching; Work and Organizational Psychology; Organizational Psychology; Industries; Cultural Economics; Cultural Theory